2013
DOI: 10.3382/ps.2013-03095
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcuma longa enhances resistance against Eimeria maxima and Eimeria tenella infections in chickens

Abstract: The effects of dietary supplementation with an organic extract of Curcuma longa on systemic and local immune responses to experimental Eimeria maxima and Eimeria tenella infections were evaluated in commercial broiler chickens. Dietary supplementation with C. longa enhanced coccidiosis resistance as demonstrated by increased BW gains, reduced fecal oocyst shedding, and decreased gut lesions compared with infected birds fed a nonsupplemented control diet. The chickens fed C. longa-supplemented diet showed enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 48 publications
3
61
0
5
Order By: Relevance
“…Emadi and Kermanshahi (2007) found that serum immunoglobulins of chickens were also affected by the inclusion of turmeric powder into the diets. The chickens fed turmeric-supplemented diet showed enhanced systemic humoral and cellular immunities (Kim et al, 2013;Lee et al, 2013). The balance between reactive oxygen species (ROS) and the cellular antioxidant defenses decides the amount of ROS in the cells (Burton and Jauniaux, 2011) leading to the formation of lipid peroxidation products such as MDA (Droge, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Emadi and Kermanshahi (2007) found that serum immunoglobulins of chickens were also affected by the inclusion of turmeric powder into the diets. The chickens fed turmeric-supplemented diet showed enhanced systemic humoral and cellular immunities (Kim et al, 2013;Lee et al, 2013). The balance between reactive oxygen species (ROS) and the cellular antioxidant defenses decides the amount of ROS in the cells (Burton and Jauniaux, 2011) leading to the formation of lipid peroxidation products such as MDA (Droge, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrientes e aditivos são rotineiramente pesquisados com a finalidade de diminuir as perdas causadas pela coccidiose (ALLEN et al, 1997;KIDD et al, 2003;PERSIA et al, 2006;ALMEIDA et al, 2012;KIM et al, 2013). A magnitude das perdas variam de acordo com a espécie da Eimeria envolvida, embora frequentemente sejam consideráveis, pelo fato de em um surto estarem envolvidas mais de uma espécie, específicas para cada região do intestino (CORNELISSEN et al, 2009).…”
Section: Resultsunclassified
“…(MIZOBUCHI e SATO, 1985). O lúpulo e o extrato de suas flores são utilizados pela indústria cervejeira para conferir o sabor e aroma da cerveja, mas eles foram inicialmente utilizados para inibir o crescimento de bactérias ácido lácticas no processo de produção desta bebida (GRUESO et al, 2013 (TIIHONEN et al, 2010;MOUNTZOURIS et al, 2011;ABDEL-WARETH et al, 2012;HASHEMI et al, 2012;KIM et al, 2013). Tiihonen et al (2010) ZHOU et al, 2007;CRESSMAN et al, 2010;OVIEDO-RONDON et al, 2010;LEE et al, 2010;LA-ONGKHUM et al, 2011) e T-RFLP (GONG et al, 2002;GEIER et al, 2010 (YUN et al, 2000).…”
Section: Desempenho Produtivo E Microbiota Intestinal De Frangos De Cunclassified
See 2 more Smart Citations